2022
DOI: 10.1111/jonm.13665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shift work on fatigue, reaction time and accuracy of nurses in the Department of Neurology: A cross‐sectional observational study

Abstract: Aims The purpose of our study was mainly to explore the effect of different shift work on cognitive and executive performance in a real clinical environment among nurses from China. Background Working in shifts can disrupt circadian rhythm, resulting in reduced sleep duration, which can have a detrimental effect on cognitive function. To provide continuous service for patient care, shift work is often a special requirement for nurses. The Stroop test can be used to measure selective attention and reaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…Among 64 studies included in the systematic review, 39 were related to the effect of shift work on cognitive functions ( Table 4 ) ( Deary and Tait, 1987 ; Orton and Gruzelier, 1989 ; Lingenfelser et al, 1994 ; Smith et al, 1995 ; Petru et al, 2005 ; Rouch et al, 2005 ; Saricaoğlu et al, 2005 ; Griffiths et al, 2006 ; Chang et al, 2011 , 2013a , b ; Anderson et al, 2012 ; Shwetha and Sudhakar, 2012 , 2014 ; Niu et al, 2013 ; Özdemir et al, 2013 ; Veddeng et al, 2014 ; Kazemi et al, 2016 , 2018 ; Maltese et al, 2016 ; Titova et al, 2016 ; Vajravelu et al, 2016 ; Haidarimoghadam et al, 2017 ; Soares and de Almondes, 2017 ; Williams et al, 2017 ; Persico et al, 2018 ; Taylor et al, 2019 ; Abdelhamid et al, 2020 ; Adams and Venter, 2020 ; Athar et al, 2020 ; James et al, 2021 ; Prasad et al, 2021 ; Stout et al, 2021 ; Sun et al, 2021 ; Zhao et al, 2021 ; An et al, 2022 ; Benítez-Provedo et al, 2022 ; Esmaily et al, 2022 ; Peng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 64 studies included in the systematic review, 39 were related to the effect of shift work on cognitive functions ( Table 4 ) ( Deary and Tait, 1987 ; Orton and Gruzelier, 1989 ; Lingenfelser et al, 1994 ; Smith et al, 1995 ; Petru et al, 2005 ; Rouch et al, 2005 ; Saricaoğlu et al, 2005 ; Griffiths et al, 2006 ; Chang et al, 2011 , 2013a , b ; Anderson et al, 2012 ; Shwetha and Sudhakar, 2012 , 2014 ; Niu et al, 2013 ; Özdemir et al, 2013 ; Veddeng et al, 2014 ; Kazemi et al, 2016 , 2018 ; Maltese et al, 2016 ; Titova et al, 2016 ; Vajravelu et al, 2016 ; Haidarimoghadam et al, 2017 ; Soares and de Almondes, 2017 ; Williams et al, 2017 ; Persico et al, 2018 ; Taylor et al, 2019 ; Abdelhamid et al, 2020 ; Adams and Venter, 2020 ; Athar et al, 2020 ; James et al, 2021 ; Prasad et al, 2021 ; Stout et al, 2021 ; Sun et al, 2021 ; Zhao et al, 2021 ; An et al, 2022 ; Benítez-Provedo et al, 2022 ; Esmaily et al, 2022 ; Peng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… Adams and Venter (2020) wanted to quantify the effects of shift work on cognitive functions in anaesthesiology trainees and observed that after 14-h night shift they had a decline in reaction time, psychomotor functions and attention. An et al (2022) explored the effects of different work shifts on cognitive and executive performance in nurses, showing that reported fatigue after the evening shift can negatively affect reaction time. Anderson et al (2012) sought to quantify the cognitive deterioration due to repeated exposure to 24- to 30-h shift and found progressive impairment due to chronic sleep deficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, nurses routinely work 8 or 12 h shifts. Although a 12 h shift may reduce the number of shifts and commuting time while also allowing for more continuous patient care, it is believed that prolonged periods of uninterrupted work are associated with increased fatigue and poor performance [9]. A study demonstrated that nurses working 12.5 h or more had more than three times the risk of errors than those who worked less than 8 h [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study in polysomnography technicians showed one 12 h night shift to be already sufficient to increase perceived sleepiness, reaction time and the number of lapses of attention [ 12 ]. Shift work, as investigated in a recent study in nurses, was shown to increase fatigue after day and evening shifts and affect the reaction time after the evening shift [ 13 ]. Nurses did not differ in accuracy and maintained a high level of attention among the three working shifts, suggesting a highly developed sense of responsibility in our nurses.…”
Section: Introductionmentioning
confidence: 99%